Therapeutic approaches to acute appendicitis in pregnancy and difficulties in its diagnosis - Carvalho Vilarouca de Freitas, Anna Karolyna; Andrade do Nascimento, Ankilma; Ramalho Tróccoli dos Santos, Arthur Elesbão; da Silva, Francisco Alírio (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2025)
Introduction: During pregnancy, the incidence rate of Acute Appendicitis (AA) ranges from 1:1,000 to 1:1,500 pregnant women. Due to the anatomical and physiological changes caused by gestation, its diagnosis is often masked; therefore, imaging exams are extremely important for diagnostic confirmation. The Brazilian Federation of Gynecology and Obstetrics (Febrasgo) emphasizes that reluctance to operate on pregnant women increases the likelihood of appendiceal rupture, raising the risk of fetal death to 20%. Objective: To identify, in recent literature, the factors that contribute to the difficulty in diagnosing AA during pregnancy and to analyze the therapeutic options available for its management. Methodology: The databases used were the BVS Regional Portal (Virtual Health Library) and PubMed (National Library of Medicine), using the following descriptors: Diagnosis, Appendicitis, Pregnancy and Surgery. The terms were combined using the Boolean operator AND, and the search was conducted between March and May 2024. After applying inclusion and exclusion criteria, 12 articles were selected for the development of this study. Results and Discussion: Analysis of the studies made it possible to identify the main topics surrounding acute appendicitis in pregnancy, such as epidemiology, symptoms, diagnostic tools, complications, and therapeutic management. The most prominent symptoms were abdominal pain, nausea, and vomiting. Additionally, the potential of scoring systems such as RIPASA, Tzanakis, Alvarado, and Ohman in the early identification of these cases was noted, as well as the relevance of exams such as Ultrasound (US) and Magnetic Resonance Imaging (MRI). The preferred approach is laparoscopy, due to its characteristics as a minimally invasive procedure. Conclusion: Due to the physiological modifications experienced by the maternal organism, a high degree of diagnostic suspicion is required for the timely diagnosis and treatment of acute appendicitis during pregnancy, in order to avoid adverse outcomes for the mother–fetus dyad.